Antimicrobial peptides Pep19–2.5 and Pep19-4LF inhibit Streptococcus mutans growth and biofilm formation. (August 2019) - Jannadi, Hanen; Correa, Wilmar; Zhang, Ze; Brandenburg, Klaus; Oueslati, Ridha; Rouabhia, Mahmoud
Abstract: With this study, we investigated the effect of synthetic antimicrobial peptides Pep19–2.5 and Pep194LF alone or in combination with antibiotics on S. mutans growth and biofilm formation/disruption. We also examined the cytotoxic effect of each peptide on monocytes. S. mutans was cultured in the presence of different concentrations of each peptide. We showed that Pep19–2.5 and Pep19-4LF were able to significantly (p ≤ 0.01) inhibit the growth of S. mutans . The synthetic peptides also decreased biofilm formation by S. mutans . Furthermore, both peptides reduced the viability of S. mutans in already formed biofilms. The combination of each peptide with antibiotics (penicillin/streptomycin, P/S) produced additive interactions which inhibited S. mutans growth and biofilm formation. Pep19–2.5 and Pep19-4LF were nontoxic, as they did not decrease monocyte viability and did not increase the lactate dehydrogenase activity of the exposed cells. In conclusion, synthetic peptides Pep19–2.5 and Pep19-4LF did inhibit S. mutans growth and its capacity to form biofilm. Both peptides were found to be nontoxic to monocytes. These data provide new insight into the efficacy of synthetic peptides Pep19–2.5 and Pep19-4LF against S. mutans . These peptides may thus be useful in controlling the adverse effects of this cariogenic bacterium in human. Highlights: The synthetic peptides Pep19–2.5 and Pep194LF inhibit the growth of S. mutans. They decreased biofilm formation by S. mutans. The combination of each peptide with penicillin produced synergistic interactions which inhibited S. Mutans growth. The Pep19–2.5 and Pep19-4LF were nontoxic to monocytes.